The Emergency Assessment and Management of Non-Suicidal Self-Injury in Adolescents - Idicula, Sindhu A.; Vyas, Amy; Garber, Nicole (Adolescent Psychiatry, 2019)
Background and Goals: Non-suicidal self-injury (NSSI) is a common presenting issue mental health providers experience in all levels of care from outpatient clinics to inpatient units. It is common among adolescents seen in emergency settings, either as a presenting problem or as a covert condition that may not be detected unless specifically assessed for. The presence of NSSI increases the risk of suicide. This article aims to help the clinician develop a better understanding of NSSI – what it may entail, the prevalence, and the motivations for why young people engage in it. Methods: We review the reasons adolescents injure themselves, the link between NSSI and psychiatric diagnoses and suicide, the assessment of NSSI, and treatment planning, with emphasis on ways to screen for NSSI and interventions that can be implemented in the Emergency Department. We illustrate the complexity of NSSI with the case of a young patient with a complex psychiatric history and an extensive history of self-injury. Results and Discussion: Despite the seeming intractability of NSSI, a number of evidencebased treatments exist. Treatment primarily involves specialized forms of psychotherapy, but interventions can be implemented in the ED that will reduce the immediate risk of NSSI while more definitive intervention is awaited. Conclusion: Mental health consultations in the ED should always include screening for NSSI. Mental health professionals in the ED can play an important role in the detection and treatment of this condition.
Keywords: non-suicidal self-injury